Seroepidemiology of Neosporosis in Various Animals in the Qinghai-Tibetan Plateau - Qi, Tongsheng; Ai, Jingkai; Yang, Jinfang; Zhu, Heng; Zhou, Yuyu; Zhu, Yulu; Zhang, Heming; Qin, Qi; Kang, Ming; Sun, Yali; Li, Jixu (Frontiers in Veterinary Science, 2022)
Neosporosis, a worldwide infectious disease, causes by intracellular parasite N. caninum that is a major pathogen of abortion in cattle and neurological disorders in other hosts. However, limited data are available on animals exposed to N. caninum in the Qinghai-Tibetan Plateau Area (QTPA) and little is known about whether these animals in the plateau area play an important role in the epidemiology of N. caninum. Therefore, the indirect ELISAs based on a combination of NcSAG1 and NcGRA7 antigens were developed to examine both N. caninum specific-IgG and -IgM antibodies in Tibetan sheep, yak, cow, pig, cattle, horse, chicken, camel, and donkey from the QTPA in this study. The results showed that all current species present IgG and IgM-positive animals, and overall seroprevalences of N. caninum were 18.6% (703/3782) and 48.1% (1820/3782) for IgG and IgM antibodies, respectively. Further analysis found significant differences from different altitudes in IgG in Tibetan sheep and IgM in the yak. Hence, the present serological results indicate that tested animal populations in the QTPA are suffering from N. caninum infections or have become carriers of N. caninum antibodies. To the best of our knowledge, this is the first report of N. caninum infected in current animals in the QTPA, the first epidemiology of neosporosis in cow and camel in China, and the first record of N. caninum IgM antibodies in all these surveyed animals in China. This study provides the latest valuable data on the epidemiology of neosporosis in China and in the plateau areas of the world.